2016
DOI: 10.1007/978-3-319-42542-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of Cancer: An Introductory Overview

Abstract: The prevalence of obesity has increased substantially in the past in almost all countries of the world, and a further increase is expected for the future. Besides the well-established effects on type 2 diabetes and cardiovascular disease, there is convincing evidence today that obesity also increases the risk of several types of cancer, including colorectal cancer, postmenopausal breast cancer, endometrial cancer, renal cell carcinoma, esophageal adenocarcinoma, pancreatic cancer, and liver cancer. Obesity pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 37 publications
1
61
0
7
Order By: Relevance
“…Notably, although the current findings indicate that a higher body fatness at a young age appears to be protective against the risk of breast cancer later in life, being overweight or obese during this period of life is not advocated because the potential detrimental role of excess body fatness in the development of chronic diseases, certain types of cancer and other health conditions far outweighs its potential protective role on breast cancer. Age is regarded as a well‐established risk factor for breast cancer because the incidence rates of breast cancer increase with age .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Notably, although the current findings indicate that a higher body fatness at a young age appears to be protective against the risk of breast cancer later in life, being overweight or obese during this period of life is not advocated because the potential detrimental role of excess body fatness in the development of chronic diseases, certain types of cancer and other health conditions far outweighs its potential protective role on breast cancer. Age is regarded as a well‐established risk factor for breast cancer because the incidence rates of breast cancer increase with age .…”
Section: Discussionmentioning
confidence: 69%
“…The connection between body fatness/adiposity and breast cancer throughout the life course is complex. In this meta‐analysis, the inverse association between higher body fatness at a young age and the risk of postmenopausal breast cancer is somewhat surprising because various measures of adiposity (BMI at cohort entry, weight gain, waist circumference and waist‐to‐hip ratio) have been largely linked to a higher risk of developing this malignancy after menopause . It is almost impossible to isolate a single factor that is fully responsible for the development of breast cancer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, patients with rapidly progressing gallbladder and bile duct cancers have a lesser chance of developing other cancers. Previous studies reported that colorectal, endometrial and breast cancers have common exogenous risk factors such as obesity/body weight gain and dietary habit . Obesity is strongly associated with endometrial cancer, but is weakly associated with postmenopausal breast cancer and colon cancer .…”
Section: Discussionmentioning
confidence: 97%
“…Plausible biological mechanisms include insulin resistance, hyperinsulinemia, chronic inflammation, altered levels of growth factors, adipocytokines and steroid hormones. In addition to its effect on colorectal cancer incidence, obesity may play a role in colorectal cancer recurrence, treatment outcomes and survival [20,21]. The adipokines adiponectin and leptin and adipocytemediated chronic low-grade inflammation represented by the acute-phase C-reactive protein may explain a substantial part of the association between obesity and risk of colorectal cancer [22].…”
Section: Discussionmentioning
confidence: 99%